Evaluation of the Influence of Principal’s Training on Security Management in Public Secondary Schools in Nzaui Sub-County, Makueni County, Kenya - Muoki, Wambua Joseph (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2017)
Many of the secondary schools have had threats to safety from within originating from fires, insect bites, loose and sharp objects, poorly constructed buildings inadequate and poorly ventilated rooms all these among others makes the learner, the teacher and the workers insecure while in school. The study aimed at assessing the influence of the principal’s training on safety management in all the public schools in Nzaui sub-County, Makueni County Kenya. A mixed method was used consequently applying the concurrent triangulation strategy. Qualitative data was thematically examined beside the research objects then presented in description forms. It was evident from the findings that insecurity was on the rise in many secondary schools in Nzaui Sub-county. It further revealed that principals’ training has not been operative in security management in public secondary schools. Thus, the study commends that the principals should develop training mechanism to promote security management in their school. The principals should allocate sufficient resources for employment and training of security staff and purchases of advanced security installations.